1982
DOI: 10.1136/vr.110.6.118
|View full text |Cite
|
Sign up to set email alerts
|

Causes of hypothermia in 89 lambs

Abstract: The causes of hypothermia in 89 lambs were identified on the basis of history and clinical biochemistry. Excessive heat loss accounted for 24 per cent of the cases, and depressed heat production because of either severe hypoxia during birth, immaturity or starvation accounted for 72 per cent. Exhaustion of energy reserves and hypoglycaemia were marked characteristics of lambs which became hypothermic after 12 hours of age. Most of the lambs were either twins or triplets. The implications of the findings for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
3

Year Published

1983
1983
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 0 publications
0
17
0
3
Order By: Relevance
“…Slee 1977Haresign etal.1977;Eales et al 1982b Bennen 1982) and has been reported to decline in newborn lambs (Alexander 1962) (Robinson et al 1986). However, the extent of hypothermia in these lambs was substantially less than the, on average, 30'C identified by shepherds with field animals (Eales et al 1982a). Alexander (1962) …”
mentioning
confidence: 80%
“…Slee 1977Haresign etal.1977;Eales et al 1982b Bennen 1982) and has been reported to decline in newborn lambs (Alexander 1962) (Robinson et al 1986). However, the extent of hypothermia in these lambs was substantially less than the, on average, 30'C identified by shepherds with field animals (Eales et al 1982a). Alexander (1962) …”
mentioning
confidence: 80%
“…Secondly, exhaustion of liver and muscle glycogen coincides with the likely (Alexander, 1962c) and the known (Eales et al 1982a;Mellor, 1983;Eales & Small, 1985) times of appearance of hypothermia in unfed lambs which have not experienced prenatal or intrapartum hypoxaemia, lower air temperatures causing an earlier appearance of hypothermia (Table 6). …”
Section: Utilization Of Body Energy Reservesmentioning
confidence: 99%
“…First, the availability of carbohydrate and not lipid is the ultimate determinant of the period during which a new-born's well being will not be threatened. Even and the resulting hypoglycaemia lead to depressed heat production which causes hypothermia and to compromised cerebral function, indicated by coma, convulsions and other symptoms (Goodwin, 1957;McCance & Widdowson, 1959;Alexander, 1962c;Cormblath & Schwartz, 1966;Shelley & Neligan, 1966;Eales, Small & Armstrong, 1980;Eales, Gilmour, Barlow & Small, 1982a;Eales, Small & Gilmour, 1982c). Hypothermia usually precedes cerebral compromise and is often the cause ofdeath in cold conditions, whereas cerebral compromise usually causes death in thermoneutral conditions.…”
Section: Utilization Of Body Energy Reservesmentioning
confidence: 99%
“…starvation. Eales, Gilmour, Barlow and Small (1982) defined two periods of high risk from neonatal hypothermia: birth to 5 h of age and 12 to 36 h of age. In the first period, the major cause of hypothermia was excessive heat loss.…”
mentioning
confidence: 99%